Program Peningkatan Kemampuan Guru Dalam Pembelajaran Bahasa Jawa di SD Patemon 01 dan SD Sekaran 01 Kecamatan Gunungpati Kota Semarang - Joko Sukoyo; Widodo Widodo (Universitas Mathla'ul Anwar Banten, 2017)
Learning Javanese language has been starting on since a long time, but still there are some problems found in the field. Problems when learning Javanese language that occur in SD Patemon 01 and SD Sekaran 01, District Gunungpati, Semarang are (1) low capacity of the teachers in creating computer-based learning media, (2) lack of language skills of the teachers in using Javanese language variety of manners, and (3) frequent occurrence of errors in the assessment of learning Javanese language. In connection with these conditions, devotee team tried to be facilitators to the problems faced by teachers in SD Patemon 01 and SD Sekaran 01 by conducting science and technology activities for the Community (IbM). IbM program implementation used workshop model with a variety of methods, such as lecturing, demonstrations, direct practice, frequently asked questions and assignments. The results of this IbM program are capacity building of teachers in making computers-based learning media for Javanese language, improving the competence of teachers in terms of manners of Javanese language skills, and increaseing understanding of Javanese language learning assessment. The increase was indicated from abilities’ score of the teachers before and after the IbM program. The ability of teachers in terms of making computer-based instructional media increased significantly, ie 16.9%. Competence of teachers in terms of unggah-ungguh based on Javanese language, especially in speaking skills manners increased 6.3%. The ability of teachers in terms of understanding of the Java language learning assessment increased 9.7%.